Li-ion battery without olefin separator
The reactive evaporation method forms a ceramic separator layer on Li-ion battery electrodes, addressing dendrite-related shorts and cost issues, resulting in improved charging speed and capacity.
Patent Information
- Application Number
- JP2022093193
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2017-08-17
- Filing Date
- 2022-06-08
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2038-07-17
AI Technical Summary
Current Li-ion battery separators are susceptible to electrical shorts due to lithium dendrite growth, are costly, and complicate manufacturing processes, limiting charging speed, capacity, and size efficiency.
A method of forming a ceramic separator layer on electrode surfaces using reactive evaporation, which involves depositing a metal material on the electrode and reacting it with a reactive gas to form a ceramic layer, reducing the need for polyolefin separators and enhancing electrical insulation.
The ceramic separator layer reduces ionic resistance, prevents dendrite growth, and improves charging speed and capacity while being more cost-effective, thus enhancing the performance and efficiency of Li-ion batteries.
Smart Images

Figure 0007599454000003 
Figure 0007599454000004 
Figure 0007599454000005
Abstract
Description
[Technical field]
[0001] SUMMARY OF THE DISCLOSURE Embodiments of the present disclosure generally relate to separators, high performance electrochemical devices, such as batteries and capacitors, that include such separators, and methods of making the same. [Background technology]
[0002] Fast-charging, high-capacity energy storage devices such as capacitors and lithium-ion (Li-ion) batteries are being used in an increasing number of applications, including portable electronics, medical, transportation, grid-tied bulk energy storage, renewable energy storage, and uninterruptible power supplies (UPS).
[0003] A Li-ion battery typically includes an anode electrode, a cathode electrode, and a separator disposed between the anode and cathode electrodes. The separator is an electronic insulator that provides physical and electrical isolation between the cathode and anode electrodes. The separator is typically made of microporous polyethylene and polyolefin. During the electrochemical reaction, i.e., during charging and discharging, Li ions are transported through the pores of the separator between the two electrodes via the electrolyte. Therefore, high porosity is desirable to increase ionic conductivity. However, some highly porous separators are susceptible to electrical shorts when lithium dendrites formed during cycling cause a short circuit between the electrodes.
[0004] Currently, battery cell manufacturers purchase separators, which are laminated in a separate process along with the anode and cathode electrodes. Other separators are typically made by wet or dry extrusion of a polymer, which is then stretched to create holes (cracks) in the polymer. Separators are also one of the most expensive components in Li-ion batteries, accounting for more than 20% of the material cost of a battery cell.
[0005] In most energy storage applications, the charging time and capacity of the energy storage device are important parameters. In addition, the size, weight, and / or cost of such energy storage devices can be significant limitations. The use of currently available commercially available separators has a number of drawbacks: such commercially available materials limit the minimum size of electrodes constructed from such materials, electrical shorts occur, manufacturing methods are complex, and materials are expensive. Furthermore, current separator designs frequently experience lithium dendrite growth, which can lead to short circuits.
[0006] Thus, there is a need in the art for faster charging, higher capacity energy storage devices with separators that are smaller, lighter, and more cost-effective to manufacture. Summary of the Invention
[0007] The embodiments of the present disclosure generally relate to separators, high performance electrochemical devices, such as batteries and capacitors, that include said separators, and methods of making the same. In one embodiment, a method of forming a separator for a battery is provided. The method includes exposing a metallic material to be deposited on a surface of an electrode structure disposed in a treatment region to an evaporation process. The method further includes flowing a reactive gas into the treatment region. The method further includes reacting the reactive gas with the evaporated metallic material to deposit a ceramic separator layer on the surface of the electrode structure.
[0008] In another embodiment, a method of forming a battery is provided. The method includes depositing a ceramic separator layer on a surface of a positive electrode structure. The ceramic separator layer is deposited on the surface of the positive electrode structure by exposing a metallic material deposited on the surface of the positive electrode structure to an evaporation process, flowing a reactive gas into a treatment region, and reacting the reactive gas with the evaporated metallic material to deposit the ceramic separator layer. The positive electrode structure is joined with a negative electrode with the ceramic separator layer therebetween.
[0009] In yet another embodiment, a method of forming a battery is provided. The method includes depositing a ceramic separator layer on a surface of a negative electrode structure. The ceramic separator layer is deposited on a surface of the negative electrode structure by exposing a metallic material deposited on the surface of the negative electrode structure to an evaporation process, flowing a reactive gas into a treatment region, and reacting the reactive gas with the evaporated metallic material to deposit the ceramic separator layer on the negative electrode structure. The negative electrode structure is joined to a positive electrode with the ceramic separator layer therebetween.
[0010] In yet another embodiment, a method of forming a battery is provided. The method includes depositing a first ceramic separator layer on a surface of a positive electrode structure. The ceramic separator layer is deposited on the surface of the positive electrode structure by exposing the metallic material deposited on the surface of the positive electrode structure to an evaporation process, flowing a reactive gas into a treatment area, and reacting the reactive gas with the evaporated metallic material to deposit the ceramic separator layer. The method further includes depositing a second ceramic separator layer on a surface of the negative electrode structure. The second ceramic separator layer is deposited on the surface of the negative electrode structure by exposing the metallic material deposited on the surface of the negative electrode structure to an evaporation process, flowing a reactive gas into a treatment area, and reacting the reactive gas with the evaporated metallic material to deposit the second ceramic separator layer on the negative electrode structure. The positive and negative electrodes are joined together to form the battery.
[0011] In yet another embodiment, a method of forming a separator for a battery is provided. The method includes exposing a metallic material to be deposited on a surface of an electrode structure disposed in a treatment area to an evaporation process. The method further includes flowing a reactive gas into the treatment area. The method further includes reacting the reactive gas with the evaporated metallic material to deposit a ceramic separator layer on the surface of the electrode structure. Flowing the reactive gas into the treatment area includes flowing moist oxygen into the treatment area.
[0012] In yet another embodiment, a method of forming a battery is provided. The method includes depositing a ceramic separator layer on a surface of a negative electrode structure. Depositing the ceramic separator layer further includes exposing a metal material deposited on a surface of the negative electrode structure disposed in a processing area to an evaporation process. Depositing the ceramic separator layer further includes flowing a reactive gas into the processing area. Depositing the ceramic separator layer further includes reacting the reactive gas with the evaporated metal material to deposit the ceramic separator layer on the surface of the negative electrode structure, and flowing the reactive gas into the processing area includes flowing moist oxygen into the processing area. The method further includes joining the negative electrode structure with a positive electrode structure with the ceramic separator layer therebetween.
[0013] In yet another embodiment, a method of forming a battery is provided. The method includes depositing a ceramic separator layer on a surface of a positive electrode structure. Depositing the ceramic separator layer includes exposing a metallic material deposited on a surface of the positive electrode structure disposed in a treatment area to an evaporation process. Depositing the ceramic separator layer further includes flowing a reactive gas into the treatment area. Depositing the ceramic separator layer further includes reacting the reactive gas with the evaporated metallic material to deposit the ceramic separator layer on the surface of the positive electrode structure. Flowing the reactive gas into the treatment area includes flowing moist oxygen into the treatment area. The method further includes joining the positive electrode structure with the negative electrode structure with the ceramic separator layer therebetween.
[0014] In order that the above-mentioned features of the present disclosure may be understood in detail, a more particular description of the above briefly summarized embodiments may be had by reference to the embodiments, some of which are illustrated in the accompanying drawings. It should be noted, however, that since the present disclosure is open to other equally effective embodiments, the accompanying drawings depict only typical embodiments of the present disclosure and therefore should not be considered as limiting the scope of the present invention. [Brief description of the drawings]
[0015] [Figure 1] 1 illustrates a cross-sectional view of one embodiment of a cell structure formed in accordance with one or more embodiments described herein. [Diagram 2] 1 illustrates a cross-sectional view of another embodiment of a cell structure formed in accordance with one or more embodiments described herein. [Diagram 3] 1 illustrates a cross-sectional view of yet another embodiment of a cell structure formed in accordance with one or more embodiments described herein. [Figure 4] 1 illustrates a cross-sectional view of yet another embodiment of a cell structure formed in accordance with one or more embodiments described herein. [Diagram 5] 1 shows a process flow diagram summarizing one embodiment of a method for forming a cell structure according to one or more embodiments described herein. [Figure 6] 1 shows a process flow diagram summarizing one embodiment of a method for forming an electrode structure according to one or more embodiments described herein. [Figure 7] 1 shows a process flow diagram summarizing one embodiment of a method for forming an electrode structure according to one or more embodiments described herein. [Figure 8] 1 shows a process flow diagram summarizing one embodiment of a method for forming an electrode structure according to one or more embodiments described herein. [Figure 9] 1 shows a schematic diagram of a web tool for forming a ceramic separator according to one or more embodiments described herein. [Figure 10A] 1 shows a scanning electron microscope (SEM) image of the uncoated cathode material. [Figure 10B] 1 shows an SEM image of an aluminum oxide coated cathode material according to embodiments described herein. [Figure 11] 1 shows an SEM image of a schematic cross-sectional view of a cell structure having a ceramic separator layer formed according to an embodiment described herein. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] For ease of understanding, the same reference numerals have been used, where possible, to designate identical elements common to the figures, and it is envisioned that elements and features of one embodiment may be beneficially incorporated in other embodiments without further recitation.
[0017] The following disclosure describes separators, high performance electrochemical cells and batteries including said separators, and methods of making the same. Specific details are presented in the following description and in Figures 1 through 11 to provide a thorough understanding of the various embodiments of the present disclosure. Other details describing well-known structures and systems often associated with electrochemical cells and batteries are not described in the following disclosure to avoid unnecessarily obscuring the description of the various embodiments.
[0018] Many of the details, dimensions, angles, and other features shown in the figures are merely illustrative of particular embodiments. Thus, other embodiments may have other details, components, dimensions, angles, and features without departing from the spirit and scope of the present disclosure. In addition, further embodiments of the present disclosure may be practiced without some of the details described below.
[0019] The embodiments described herein will be described in detail below with reference to a rapid evaporation process that can be performed using a roll-to-roll coating system, such as TopMet®, SmartWeb®, or TopBeam® (all of which are available from Applied Materials, Inc., Santa Clara, Calif.). Other tools capable of performing rapid evaporation processes may also be adapted to benefit from the embodiments described herein. In addition, any system that allows for the rapid evaporation process described herein may be used to advantage. The apparatus description described herein is exemplary and should not be understood or construed as limiting the scope of the embodiments described herein. Also, although described as a roll-to-roll process, it should be understood that the embodiments described herein may also be performed on individual polymer substrates.
[0020] The term "about" generally indicates within a range of up to ±0.5%, 1%, 2%, 5%, or ±10% of the indicated value. For example, a pore size of about 10 nm generally indicates 10 nm ±10%, i.e., 9.0-11.0 nm, in the broadest sense. In addition, the term "about" can indicate either measurement error (i.e., due to limitations of the measurement method) or, alternatively, the variation or average of a physical property of a group (e.g., a population of pores).
[0021] The term "crucible" as used herein is to be understood as a unit capable of evaporating a material fed into the crucible when the crucible is heated. In short, a crucible is defined as a unit adapted to convert a solid material into vapor. Within the scope of the present disclosure, the terms "crucible" and "evaporation unit" are used synonymously.
[0022] Currently available generations of batteries, especially Li-ion batteries, use porous polyolefin separators that are susceptible to thermal contraction as temperatures rise, which can cause short circuits between the positive and negative electrodes or between the corresponding current collectors. In addition, some polyolefin separators have issues with poor wettability. A ceramic coating on the separator helps prevent direct contact between the electrodes and also helps prevent potential dendrite growth associated with Li metal. Current state-of-the-art ceramic coatings use wet coating (e.g., slot-die technology) of ceramic particles dispersed in a polymer binder to create a composite and a solvent to create a slurry. The thickness of the coating is typically around 3 microns, including randomly oriented dielectric material bound by the polymer leading to a random pore structure. Existing ceramic particle coating methods have difficulty reducing the twisting due to this random orientation of the ceramic particles. Furthermore, it is also difficult to reduce the thickness of current ceramic coatings using current wet coating techniques. To compensate for the increased surface area of fine ceramic powder particles, current wet coating techniques include increasing the amount of binders and solvents to reduce the viscosity of the slurry. Thus, current wet coating techniques suffer from several problems.
[0023] From a manufacturing point of view, in-situ deposition of ceramic coatings by dry methods is preferred from both cost and performance standpoints. In the present disclosure, a thin low ionic resistance ceramic coating is formed directly on the surface of the positive electrode and / or the surface of the negative electrode, and the ceramic coating is formed by a dry method using reactive evaporation of metals or metal compounds. Furthermore, the ceramic coating can be tailored with respect to suitable thickness, micro / nano structure, multi-layer structure, morphology, pore structure and pore / ceramic orientation.
[0024] Compared with conventional ceramic-coated separators, the reactive evaporation technology described herein has at least one of the following advantages: (1) Thinner separators reduce the volume fraction of inactive components, correspondingly increasing energy density and decreasing ionic resistance throughout the separator; (2) Controlling the coating thickness and morphology reduces tortuous pores, leading to improved separator performance; (3) Ceramic pore surfaces increase ionic conductivity throughout the electrolyte; (4) Properly designed ceramic-coated separators will enhance X-ray detection to determine manufacturing defects; (5) Higher voltage stability and puncture resistance of the separator can be achieved through nanocomposite coating control; The lithium dendrite inhibition properties of ceramic-coated separators are enhanced through nanosurface technology, achieving uniform lithium metal deposition and exfoliation during cycling.
[0025] Results achieved to date include: (1) uniform 300 nm and 600 nm thick AlO x The coating was deposited on the positive electrode using aluminum evaporation in an active oxygen environment. (2) Scotch tape peel test showed that AlO x The coating appears to adhere well. (3) Columnar AlO x The structures and crystallites are vertically aligned within the ceramic separator layer.
[0026] FIG. 1 illustrates a cross-sectional view of one embodiment of a cell structure 100 formed according to embodiments described herein. The cell structure 100 has one or more ceramic separator layers 130 formed according to embodiments described herein. In some embodiments, the cell structure 100 is a Li-ion battery structure. The cell structure 100 has a positive current collector 110, positive electrode(s) 120a, 120b (collectively 120) formed on either side of the positive current collector 110, one or more ceramic separator layers 130a-c (collectively 130), a negative current collector 150, and negative electrode(s) 140a, 140b (collectively 140) formed on either side of the negative current collector. Note that while the current collector is shown in FIG. 1 as extending beyond the stack, it is not necessary for the current collector to extend beyond the stack, and the portion that extends beyond the stack may be used as a tab. In addition, although a dual-sided electrode structure is shown, the embodiments described herein are also applicable to single-sided electrode structures.
[0027] The current collectors 110, 150 on the positive electrode 120 and the negative electrode 140, respectively, can be the same electronic conductor or different electronic conductors. Examples of metals from which the current collectors 110, 150 can be constructed include aluminum (Al), copper (Cu), zinc (Zn), nickel (Ni), cobalt (Co), tin (Sn), silicon (Si), manganese (Mn), magnesium (Mg), alloys thereof, and combinations thereof. In one embodiment, at least one of the current collectors 110, 150 is perforated. Furthermore, the current collectors can be of any form factor (e.g., metal foil, sheet, or plate), shape, and micro / macro structure. Generally, in prismatic cells, the tabs are formed of the same material as the current collectors and may be formed during stack fabrication or added later. All components except the current collectors 110 and 150 contain the lithium ion electrolyte.
[0028] The negative electrode 140 or anode can be any material compatible with the positive electrode 120. The negative electrode 140 can have an energy capacity of 372 mAh / g or more, preferably 700 mAh / g or more, and most preferably 1000 mAh / g or more. The negative electrode 140 can be composed of graphite, silicon-containing graphite (e.g., graphite mixed with silicon (<5%)), lithium metal foil or lithium alloy foil (e.g., lithium aluminum alloy), or a mixture of lithium metal and / or lithium alloy with materials such as carbon (e.g., coke, graphite), nickel, copper, tin, indium, silicon, oxides thereof, or combinations thereof. The negative electrode 140 includes an intercalation compound containing lithium or an insertion compound containing lithium.
[0029] The positive electrode 120 or cathode may be any material compatible with the negative electrode 140 and may include an intercalation compound, an insertion compound, or an electrochemically active polymer. Suitable intercalation materials include, for example, lithium-containing metal oxides, MoS2, FeS2, MnO2, TiS2, NbSe3, LiCoO2, LiNiO2, LiMnO2, LiMn2O4, VO 13 and V2O5. Suitable polymers include, for example, polyacetylene, polypyrrole, polyaniline, and polythiophene. The positive electrode 120 or cathode may be made from a layered oxide such as lithium cobalt oxide, an olivine such as lithium iron phosphate, or a spinel such as lithium manganese oxide. Exemplary lithium-containing oxides are layered, such as lithium cobalt oxide (LiCoO2), or LiNi x Co 1-2x MnO2, LiNiMnCoO2 (“NMC”), LiNi 0.5 Mn 1.5 O4, Li(Ni 0.8 Co 0.15 Al 0.05)O2, mixed metal oxides such as LiMn2O4, and doped lithium rich layered-layered materials, where x is zero or a non-zero number. An exemplary phosphate may be ferroolithite (LiFePO4), which is a variant (LiFe (1-x) Mg x PO4, etc.), LiMoPO4, LiCoPO4, LiNiPO4, Li3V2(PO4)3, LiVOPO4, LiMP2O7, or LiFe 1.5 P2O7, where x is zero or a non-zero number. Exemplary fluorophosphates can be LiVPO4F, LiAlPO4F, Li5V(PO4)2F2, Li5Cr(PO4)2F2, Li2CoPO4F, or Li2NiPO4F. Exemplary silicates can be Li2FeSiO4, Li2MnSiO4, or Li2VOSiO4. An exemplary non-lithium compound is Na5V2(PO4)2F3.
[0030] In some embodiments, the positive electrode 120 is formed from positive electrode particles. In some embodiments, the positive electrode particles are coated to promote higher voltage stability, interfacial compatibility with the electrolyte, and longer battery cycle life. Coating the positive electrode particles can be performed by sol-gel techniques, dry coating of nanoparticles onto the positive electrode material, or atomic layer deposition (ALD) techniques.
[0031] In some implementations of lithium-ion cells according to the present disclosure, lithium is contained in atomic layers of a crystal structure, for example, carbon graphite (LiC6) in the negative electrode 140 and lithium manganese oxide (LiMnO4) or lithium cobalt oxide (LiCoO2) in the positive electrode 120, although in some implementations the negative electrode 140 may also include lithium absorbing materials such as silicon, tin, etc. The cells are shown as planar structures, but may be formed into a cylinder by rolling a stack of layers, and other cell configurations (e.g., prismatic cells, button cells) may also be formed.
[0032] The electrolytes injected into the cell components 120, 130, and 140 can be composed of liquid / gel or solid polymer and can be different. In some embodiments, the electrolyte mainly comprises a salt and a medium (e.g., in a liquid electrolyte, the medium is referred to as a solvent, and in a gel electrolyte, the medium can be a polymer matrix). The salt can be a lithium salt. The lithium salt can include, for example, LiPF6, LiAsF6, LiCF3SO3, LiN(CF3SO3)3, LiBF6, and LiClO4, BETTE electrolyte (commercially available from 3M Corp., Minneapolis, Minnesota), and combinations thereof. Solvents can include, for example, ethylene carbonate (EC), propylene carbonate (PC), EC / PC, 2-MeTHF (2-methyltetrahydrofuran) / EC / PC, EC / DMC (dimethyl carbonate), EC / DME (dimethylethane), EC / DEC (dimethyl carbonate), EC / EMC (ethyl methyl carbonate), EC / EMC / DMC / DEC, EC / EMC / DMC / DEC / PE, PC / DME, and DME / PC. Polymer matrices can include, for example, PVDF (polyvinylidene fluoride), PVDF:THF (PVDF:tetrahydrofuran), PVDF:CTFE (PVDF:chlorotrifluoroethylene), PAN (polyacrylonitrile), and PEO (polyethylene oxide).
[0033] In some implementations, the ceramic separator layer 130 comprises a porous (e.g., microporous) ceramic layer (e.g., separator membrane) 130 having pores. In some implementations, the ceramic separator layer 130 is non-porous. In some implementations, the ceramic separator layer 130 comprises a lithium ion conductive material. The lithium ion conductive material can be a lithium ion conductive ceramic or a lithium ion conductive glass or liquid crystal. In some implementations, the ceramic separator layer 130 does not need to be ionically conductive, but when filled with an electrolyte (liquid, gel, solid, combinations thereof, etc.), the combination of the porous ceramic and the electrolyte is ionically conductive. The ceramic separator layer 130 is adapted to at least prevent electronic shorting (e.g., direct or physical contact between the anode and cathode) and inhibit dendrite growth. The ceramic separator layer 130 may be adapted to at least inhibit (or block) ionic conductivity (or flow) between the anode and cathode during a thermal runaway event. The ceramic separator layer 130 must be sufficiently conductive to allow ions to flow between the anode and cathode so that a selected amount of electrical current can be generated by the cell. The ceramic separator layer 130 should adhere well to the underlying electrode material, i.e., separation should not occur. As described herein, the ceramic separator layer 130 is formed over the underlying electrodes using evaporation techniques.
[0034] The ceramic separator layer 130 includes one or more ceramic materials. The ceramic material can be an oxide. Examples of the ceramic material include aluminum oxide (Al2O3), AlO x , AlOxNy, AlN (aluminum deposited in a nitrogen environment), aluminum oxide hydroxide ((AlO(OH)) (e.g., diaspore ((α-AlO(OH))), boehmite TIFF0007599454000001.tif7170, or accdalite (5Al2O3·H2O)), calcium carbonate (CaCO3), titanium dioxide (TiO2), SiS2, SiPO4, silicon oxide (SiO2), zirconium oxide (ZrO2), MgO, TiO2, Ta2O5, Nb2O5, LiAlO2, BaTiO3, BN, ion conducting garnets, ion conducting perovskites, ion conducting antiperovskites, porous glass ceramics, and the like, or combinations thereof. In one embodiment, the ceramic material is a material selected from the group consisting of porous aluminum oxide, porous-ZrO2, porous-SiO2, porous-MgO, porous-TiO2, porous-Ta2O5, porous-Nb2O5, porous-LiAlO2, porous-BaTiO3, ion-conducting garnets, ion-conducting antiperovskites, porous glass dielectrics, or combinations thereof. The ceramic separator layer 130 is a ceramic layer that does not include a binder. In some embodiments, the ceramic separator layer 130 is a porous aluminum oxide layer.
[0035] In some embodiments, the ceramic separator layer 130 may be a lithium ion conductive material. The lithium ion conductive material may be a lithium ion conductive ceramic, a lithium ion conductive glass, or an ion conductive liquid crystal. The Li ion conductive material may be, for example, LiPON, a doped variant of either the crystalline or amorphous phase of Li7La3Zr2O12, a doped antiperovskite composition, Li2S-P2S5, Li10GeP2S12, and Li3PS4, lithium phosphate glass, sulfide glass, (1-x)LiI-(x)Li4SnS4, xLiI-(1-x)Li4SnS4, a mixed electrolyte of sulfide and oxide (crystalline LLZO, an amorphous (1-x)LiI-(x)Li4SnS4 mixture, and one or more of amorphous (x)LiI-(1-x)Li4SnS4. In one embodiment, x is between 0 and 1 (e.g., 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9). The Li ion conductive material can be deposited directly on the lithium metal film using physical vapor deposition (PVD), chemical vapor deposition (CVD), spraying, doctor blade, printing, or any of many coating methods. A method suitable for some embodiments is PVD. In some embodiments, the ceramic separator layer 130 need not be ion conductive, but when filled with an electrolyte (liquid, gel, solid, combinations thereof, etc.), the combination of the porous substrate and the electrolyte becomes ion conductive.
[0036] In one embodiment, the ceramic separator layer 130 is a lithium ion conductive material, and the lithium ion conductive material is selected from the group consisting of: LiPON, garnet-type Li7La3Zr2O 12 in either the crystalline or amorphous phase, LISICON (e.g., Li 2+2x Zn 1-x GeO4 (0 < x < 1)), NASICON (e.g., Na 1+x Zr2Si x P 3-x O 12(0 < x < 3)), lithium borohydride (LiBH4), doped antiperovskite compositions, lithium-containing sulfides (e.g., Li2S, Li2S-P2S5, Li 10 GeP2S 12 and Li3PS4), as well as lithium argyrodite (e.g., LiPS5X (x is Cl, Br, or I)).
[0037] In some embodiments, the ceramic separator layer 130 comprises from about 50 wt% to about 100 wt% aluminum oxide (e.g., from about 75 wt% to about 100 wt%, from about 85 wt% to about 100 wt% aluminum oxide) based on the total weight of the ceramic separator layer 130.
[0038] In some embodiments, the ceramic material is mixed with a glass evaporated in an oxidizing atmosphere. For example, SiO2 can be introduced into Al2O3 to modify the physical properties (such as flexibility, fracture toughness, etc.) of the ceramic layer.
[0039] In some embodiments, the ceramic separator layer 130 includes a plurality of ceramic columnar protrusions. The ceramic columnar protrusions can have a diameter that extends from the bottom of the columnar protrusion (e.g., where the columnar protrusion contacts the porous substrate) to the top of the columnar protrusion. The ceramic columnar protrusions typically contain dielectric particles. Nanostructured contours or channels are typically formed between the dielectric particles.
[0040] In some embodiments, the ceramic post-shaped protrusions may include one or more of a variety of porous shapes. In some embodiments, the post-shaped protrusions of the ceramic separator layer 130 form a nanoporous structure between the post-shaped protrusions of the dielectric material. In one embodiment, the nanoporous structure may have a plurality of nanopores sized to have an average pore size or diameter of less than 10 nanometers (e.g., about 1 nanometer to about 10 nanometers, about 3 nanometers to 5 nanometers). In another embodiment, the nanoporous structure may have a plurality of nanopores sized to have an average pore size or diameter of less than about 5 nanometers. In one embodiment, the nanoporous structure has a plurality of nanopores with a diameter in the range of about 1 nanometer to about 20 nanometers (e.g., about 2 nanometers to about 15 nanometers, or about 5 nanometers to about 10 nanometers). The nanoporous structure significantly increases the surface area of the ceramic separator layer 130. The pores of the nanoporous structure can act as liquid electrolyte reservoirs and provide excess surface area for ionic conductivity. Without being bound by theory, it is believed that the electrolyte liquid / gel trapped within the nanoporous structure acts similarly to a solid electrolyte.
[0041] In some embodiments, the ceramic separator layer 130 is at least 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, or 65% more porous than a solid membrane formed from the same material, and up to at least 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, or 70% more porous than a solid membrane formed from the same material.
[0042] Porosity is commonly used because it is easy to estimate. However, tortuosity is a direct measure to describe the lithium diffusion path. Tortuosity indicates the twisted path that lithium diffuses through in the porous medium. For example, if the diffusion is along a straight path, the tortuosity is equal to 1. Due to the complex geometries (e.g., irregular grain shapes, wide range of grain size distribution, etc.) in the dielectric layer, tortuosity is not easily measured. It is believed to be desirable to introduce direct technological tortuosity, i.e., "straight" paths or channels. Ceramic layers formed using the evaporation process disclosed herein exhibit low tortuosity when compared to ceramic layers formed using currently known slot-die or other slurry deposition techniques.
[0043] The ceramic separator layer 130 can be a coating or a discrete layer having a thickness in the range of 1 nanometer to 3000 nanometers (e.g., in the range of 10 nanometers to 600 nanometers, in the range of 50 nanometers to 200 nanometers, in the range of 100 nanometers to 150 nanometers).
[0044] FIG. 2 illustrates a cross-sectional view of another embodiment of a cell structure 200 formed according to embodiments described herein. In some embodiments, the cell structure 200 is a Li-ion battery structure. Like the cell structure 100, the cell structure 200 has a ceramic separator layer 130 formed according to embodiments described herein. However, in addition to the ceramic separator layer 130, the cell structure 200 also includes one or more gel polymer layers 210a, 210b (collectively 210) disposed between the ceramic separator layer 130 and an opposing electrode structure (in this embodiment, the negative electrode 140a). Although shown contacting the positive electrode 120b, it should be understood that in some embodiments, the ceramic separator layer 130a contacts the negative electrode 140a and the gel polymer layer 210a contacts the negative electrode 140a. Without being bound by theory, it is believed that the gel polymer layers, when bonded together, help improve adhesion between the positive and negative electrodes.
[0045] The polymer of the gel polymer layer 210 can be selected from polymers currently used in the Li-ion battery industry. Examples of polymers that can be used to form the gel polymer layer include, but are not limited to, polyvinylidene difluoride (PVDF), polyethylene oxide (PEO), polyacrylonitrile (PAN), carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR), and combinations thereof. Without being bound by theory, it is believed that the gel polymer layer 210 can absorb Li-conductive electrolyte to form a gel during device fabrication, which is beneficial for forming a good solid electrolyte interface (SEI) and also helps reduce resistance. In some embodiments, a mixture of warm liquid and lithium ion conductive salt is used to make the gel electrolyte or liquid crystal electrolyte. The warm liquid mixture is injected into the spirally wound electrode or stacked electrode to fill the pores of the network electrode, and the electrolyte forms a solid or gel at room temperature. The gel polymer layer 210 can be formed by dip coating, slot die coating, gravure coating, or printing. The polymers can also be deposited using Applied Materials Metacoat equipment. The dielectric polymer layer can have a thickness of about 5 nanometers to about 1 micrometer. Organic polymers containing sulfur ions (e.g., polyphenylene sulfide with Li2O mixtures) have shown good results with lithium metal-based anodes and in some cases form liquid crystal electrolytes.
[0046] FIG. 3 illustrates a cross-sectional view of another embodiment of a cell structure 300 formed according to embodiments described herein. In some embodiments, the cell structure 300 is a Li-ion battery structure. Similar to the cell structure 200, the cell structure 300 includes one or more ceramic separator layers 330a-c (collectively 330) and one or more gel polymer layers 310a, 310b (collectively 310) formed according to embodiments described herein. The one or more ceramic separator layers 330 are similar to the one or more ceramic separator layers 130. The one or more gel polymer layers 310 are similar to the one or more gel polymer layers 210. However, the gel polymer layer 310a is disposed or "sandwiched" between the ceramic separator layers 330a and 330b.
[0047] FIG. 4 illustrates a cross-sectional view of yet another embodiment of a cell structure 400 formed according to one or more embodiments described herein. In some embodiments, the cell structure 400 is a Li-ion battery structure. Similar to the cell structure 300, the cell structure 400 has one or more ceramic separator layers 430a-c (collectively 430) and one or more gel polymer layers 440a, 440b (collectively 440) formed according to embodiments described herein. The one or more ceramic separator layers 430 are similar to the one or more ceramic separator layer(s) 130. The one or more gel polymer layers 440a, 440b (collectively 440) are similar to the one or more gel polymer layers 210. However, the gel polymer layer 440a is disposed or "sandwiched" between the ceramic separator layer 430a and the ceramic separator layer 430b. Cell structure 400 optionally includes a pre-lithiation layer 410 and a protective film 420 formed between a ceramic separator layer 430 and the pre-lithiation layer 410. Thus, instead of depositing the ceramic separator layer directly on the negative electrode as shown in Figures 1-3, ceramic separator layer 430 is deposited directly onto either the protective film 420 (if present) or the pre-lithiation layer 410 if protective film 420 is not present.
[0048] In some embodiments, the pre-lithiation layer 410 formed on the negative electrode 140a is a lithium metal film. The lithium metal film can be formed according to embodiments described herein. In some embodiments, the negative electrode 140a is a silicon graphite anode or a silicon oxide graphite anode with a lithium metal film formed thereon. The lithium metal film replenishes the lithium lost from the first cycle capacity loss of the negative electrode 140a. The lithium metal film can be a thin lithium metal film (e.g., 20 microns or less, about 1 micron to about 20 microns, or about 2 microns to about 10 microns). In some embodiments where the lithium metal film functions as the negative electrode, the lithium metal film replaces the negative electrode 140. In some embodiments where the lithium metal film functions as the negative electrode, the lithium metal film is formed on the negative current collector 150.
[0049] In some embodiments, the protective membrane 420 is formed on the lithium metal membrane. The protective membrane 420 is typically not formed in situ on the lithium metal membrane. The protective membrane 420 is electrically insulating but sufficiently conductive to lithium ions. In one embodiment, the protective membrane 420 is a non-porous membrane. In another embodiment, the protective membrane 420 is a porous membrane. In one embodiment, the protective membrane 420 has a plurality of nanopores sized to have an average pore size or diameter of less than about 10 nanometers (e.g., from about 1 nanometer to about 10 nanometers, from about 3 nanometers to about 5 nanometers). In another embodiment, the protective membrane 420 has a plurality of nanopores sized to have an average pore size or diameter of less than about 5 nanometers. In one embodiment, the protective membrane 420 has a plurality of nanopores having diameters in the range of about 1 nanometer to about 20 nanometers (eg, about 2 nanometers to about 15 nanometers, or about 5 nanometers to about 10 nanometers).
[0050] The overcoat 420 may be a coating or a separate layer having a thickness in the range of 1 nanometer to 200 nanometers (e.g., in the range of 5 nanometers to 200 nanometers, in the range of 10 nanometers to 50 nanometers). Without being bound by theory, it is believed that an overcoat greater than 200 nanometers may increase resistance within a rechargeable battery.
[0051] Examples of materials that may be used to form the protective film 420 include, but are not limited to, lithium fluoride (LiF), aluminum oxide, lithium carbonate (Li2CO3), and combinations thereof. In one embodiment, the protective film 420 is a lithium fluoride film. Without being bound by theory, it is believed that the protective film 420 can absorb Li conductive electrolyte to form a gel during device fabrication, which is beneficial for forming a good solid electrolyte interface (SEI) and also helps to lower the resistance. The protective film 420 can be deposited directly on the lithium metal film by physical vapor deposition (PVD), such as evaporation or sputtering, specialized atomic layer deposition (ALD), slot-die process, thin film transfer process, or three-dimensional lithium printing process. PVD is the preferred method for deposition of the protective film 420. The protective film 420 can also be deposited using a Metacoat instrument.
[0052] The ceramic separator layer 430a may be deposited directly on either the protective film 420 (if present) or the layer 410 before lithiation in the case where the protective film 420 is absent. The ceramic separator layer 430a may be a lithium ion conductive material. The lithium ion conductive material may be a lithium ion conductive ceramic or a lithium ion conductive glass. The Li ion conductive material may consist of, for example, one or more of LiPON, a doped variant of either the crystalline or amorphous phase of Li7La3Zr2O12, a doped antiperovskite composition, Li2S-P2S5, Li10GeP2S12, and Li3PS4, lithium phosphate glass, (1-x)LiI-(x)Li4SnS4, xLiI-(1-x)Li4SnS4, a mixed electrolyte of sulfide and oxide (crystalline LLZO, amorphous (1-x)LiI-(x)Li4SnS4 mixture, and amorphous xLiI-(1-x)Li4SnS4). In one embodiment, x is between 0 and 1 (e.g., 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9). The Li ion conductive material can be deposited directly on the layer 410 before lithiation or the protective film 420 using any of physical vapor deposition (PVD), chemical vapor deposition (CVD), spraying, doctor blade, printing, or many coating methods. A method suitable for some embodiments is PVD. In some embodiments, the ceramic separator layer 430a need not be ion conductive, but when filled with an electrolyte (liquid, gel, solid, combinations thereof, etc.), the combination of the porous substrate and the electrolyte becomes ion conductive.
[0053] In one embodiment, the ceramic separator layer 430a is a lithium ion conductive material, and the lithium ion conductive material is selected from the group consisting of. LiPON, garnet-type Li7La3Zr2O 12 of the crystalline or amorphous phase, LISICON (e.g., Li 2+2x Zn 1-x GeO4 (0 < x < 1)), NASICON (e.g., Na 1+x Zr2Si x P3-x O 12 (0 < x < 3)), lithium borohydride (LiBH4), doped antiperovskite compositions, lithium-containing sulfides (e.g., Li2S, Li2S-P2S5, Li 10 GeP2S 12 and Li3PS4), as well as lithium argyrodites (e.g., LiPS5X (x is Cl, Br, or I)).
[0054] In one embodiment, the ceramic separator layer 430a formed on the negative electrode 140 and the ceramic separator layer 430b formed on the positive electrode 120 are of different materials. For example, in one embodiment, the ceramic separator layer 430a is a non-porous lithium ion conductive material, and the ceramic separator layer 430b is a porous lithium ion conductive material.
[0055] In some embodiments, the ceramic separator layer 430 is a non-porous ion conductive electrolyte layer, which can provide additional electrochemical stability to some anode material compositions. For example, in one embodiment, the negative electrode 140 is a silicon or silicon oxide mixed graphite anode material with a pre-lithiated layer 410 (e.g., a lithium metal film) formed on top, a protective film 420 that is a lithium fluoride film, and the ceramic separator layer 430 is a non-porous lithium ion conductive material.
[0056] In some embodiments, prior to method 500 (see FIG. 5), method 600 (see FIG. 6), or method 700 (see FIG. 7), the surface of the electrode (e.g., the negative electrode and / or the positive electrode) is optionally exposed to a surface modification treatment to enhance nucleation / growth conditions on the surface of the electrode. In some embodiments, the surface modification treatment process is a plasma treatment process (e.g., a corona discharge treatment process). The surface modification treatment process includes supplying a treatment gas mixture into a treatment region. A plasma is then formed from the treatment gas mixture to plasma treat the surface of the electrode and activate at least a portion of the electrode to an excited state to form a treated electrode having a treated upper surface, which may enhance nucleation / growth conditions for a subsequently deposited ceramic separator layer.
[0057] In one embodiment, the process gas mixture includes at least one of an oxygen-containing gas, an inert gas (e.g., argon, helium), or a combination thereof. In one embodiment, the oxygen-containing gas provided in the process region includes oxygen (O), ozone (O), oxygen radicals (O * ), ionized oxygen atoms, carbon dioxide (CO2), nitric oxide (NO x ), water vapor, or a combination thereof. Other oxygen-containing gases may be used.
[0058] According to one embodiment of the present disclosure involving oxidation, a gas source supplies oxygen gas (O2) through a mass flow controller to an ozone generator, which converts most of the oxygen into ozone gas (O3). The resulting oxygen-based mixture of O2 and O3, and possibly some oxygen radicals O * The ionized oxygen atoms or molecules are then delivered to a treatment region where the oxygen-based gas reacts with the surface of an electrode, which is heated to a predetermined, preferably low, temperature. Ozone is reacted with the surface of the electrode through the reaction O3 → O2 + O * is a metastable molecule that spontaneously and rapidly dissociates at *is a radical and reacts very rapidly with available substances that are oxidizable. Ozone generators can be implemented in many forms, including capacitively or inductively coupled plasma, or UV lamp sources.
[0059] At these high ozone concentrations, less heating of the electrode is required to achieve a relatively high oxidation rate. Also, because of the high ozone concentration, the ozone partial pressure can be reduced. Because of the high percentage of ozone, the oxidation of ozone can be carried out at pressures below 20 Torr. It should be understood that the above surface modification techniques are exemplary and other surface modification techniques may be used to achieve the selected surface modification. For example, in some embodiments, the preparation may include exposing the electrode to a corona treatment, chemically treating the electrode (e.g., with an oxidizing agent), or adsorbing or grafting a polyelectrolyte to the surface of the electrode. It may be suitable to have a charged electrode so that a first layer of oppositely charged material is attached to the electrode.
[0060] In some embodiments, the surface modification process is an electron beam treatment process. An electron beam source is directed to the surface of the electrode before coating the electrode. The electron beam source can be a linear source. The electron beam device that emits the electron beam is usually adapted to have the electron beam impact the electrode over its entire width, so that the longitudinal movement of the electrode causes the entire surface (one side) of the electrode to be treated with the electron beam. The electron beam device can be an electron source, such as an electron flood gun, a linear electron gun, or an electron beam. The gas used in the electron source can be argon, O2, N2, CO2, or He, more specifically O2, N2, CO2, or He.
[0061] The electrode treated with the emitted electrons is physically, respectively structurally, modified to achieve improved adhesion between the electrode and the subsequently deposited ceramic separator layer. The selected effect can be achieved by providing electrons with an energy of 1 keV to 15 keV, more typically 5 keV to 10 keV, e.g. 6 keV, 7 keV, 8 keV or 9 keV. Typical electron currents are 20 mA to 1500 mA, e.g. 500 mA.
[0062] In some implementations, prior to method 500 (see FIG. 5), method 600 (see FIG. 6), method 700 (see FIG. 7), or method 800 (see FIG. 8), the surface of the electrodes (e.g., the negative electrode and / or the positive electrode) is optionally subjected to a cooling process. In one implementation, the surface of the electrode structure may be cooled to a temperature between −20 degrees Celsius and room temperature (i.e., 20 to 22 degrees Celsius) (e.g., a temperature between −10 degrees Celsius and 0 degrees Celsius). In some implementations, the electrode structure may be cooled by cooling the drum on which the electrode structure moves. Other active cooling means may be used to cool the electrode structure. During the evaporation process, the electrode structure may be exposed to temperatures in excess of 1000 degrees Celsius, so it is beneficial to cool the electrode structure prior to the evaporation process of operations 510, 610, and 710.
[0063] 5 shows a process flow diagram summarizing one embodiment of a method 500 for forming a cell structure in accordance with one or more embodiments described herein. The cell structure can be, for example, the cell structure 100 shown in FIG.
[0064] In operation 510, the material to be deposited on at least one of the surfaces of the negative electrode and the positive electrode is subjected to an evaporation process to evaporate the material to be deposited on the processing region. In some implementations, the negative electrode is the negative electrode 140 and the positive electrode is the positive electrode 120. In some implementations, the material to be deposited is deposited on a single electrode (e.g., either the negative electrode or the positive electrode). In some implementations, the material to be deposited is deposited on both the negative electrode and the positive electrode. In some implementations, deposition on the negative electrode and the positive electrode may occur in the same processing chamber or in separate processing chambers. In some implementations, deposition on the negative electrode and the positive electrode may occur sequentially or simultaneously.
[0065] The evaporation material may be selected from the group consisting of aluminum (Al), zirconium (Zr), hafnium (Hf), niobium (Nb), tantalum (Ta), titanium (Ti), yttrium (Y), lanthanum (La), silicon (Si), boron (B), silver (Ag), chromium (Cr), copper (Cu), indium (In), iron (Fe), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), nickel (Ni), tin (Sn), ytterbium (Yb), lithium (Li), calcium (Ca) or combinations thereof. Typically, the material to be deposited is a metal, such as aluminum or an aluminum alloy. Furthermore, the evaporation material may also be an alloy of two or more metals. The evaporation material is a material that evaporates during evaporation and coats the surface of one or more electrodes. The material to be deposited (e.g., aluminum) may be provided in a crucible. For example, aluminum can be evaporated by thermal evaporation techniques or by electron beam evaporation techniques.
[0066] In some embodiments, the evaporation material is fed to the crucible as a wire. In this case, the feed rate and / or wire diameter must be selected so that the appropriate ratio of evaporation material to reactive gas is achieved. In some embodiments, the diameter of the feed wire for feeding to the crucible is selected between 0.5 mm and 2.0 mm (e.g., between 1.0 mm and 1.5 mm). These dimensions may refer to several feed wires made of the evaporation material. Typical feed rates for the wire are in the range between 50 cm / min and 150 cm / min (e.g., between 70 cm / min and 100 cm / min).
[0067] The crucible is heated to generate vapor, which reacts with the reactive gas provided in operation 510 and coats the surface of the one or more electrodes with a ceramic separator layer (e.g., ceramic separator layer 130). Typically, the crucible is heated by applying a voltage to the electrodes of the crucible, which are disposed on opposite sides of the crucible. Generally, according to the embodiments described herein, the crucible material is electrically conductive. Typically, the material used as the crucible material is temperature resistant up to the temperatures used for melting and evaporation. Typically, the crucible of the present disclosure is made from one or more materials selected from the group consisting of metal borides, metal nitrides, metal carbides, non-metal borides, non-metal nitrides, non-metal carbides, nitrides, titanium nitrides, borides, graphite, TiB2, BN, B4C, and SiC.
[0068] The material to be deposited is melted and evaporated by heating the evaporation crucible. Heating can be performed by providing a power source (not shown) connected to a first electrical connection and a second electrical connection of the crucible. For example, these electrical connections can be electrodes made of copper or a copper alloy. Heating is thus performed by an electric current flowing through the body of the crucible. According to other embodiments, heating can also be performed by a radiant heater of the evaporation device or an inductive heating unit of the evaporation device.
[0069] The evaporation unit according to the present disclosure can be heated to a temperature between 1300 and 1600 degrees Celsius, for example 1560 degrees Celsius. This is done by appropriately adjusting the current through the crucible or by appropriately adjusting the radiation. The crucible material is usually selected so that its stability is not adversely affected by the temperature in that range. The speed of the electrode or electrodes is usually in the range between 20 and 200 cm / min, more typically in the range between 80 and 120 cm / min, such as 100 cm / min. In these cases, the means for transport should be capable of transporting the substrate at these speeds.
[0070] In operation 520, a reactive gas is flowed into the processing region to react with the evaporated material to form a ceramic separator layer on at least the surface of the negative electrode and the surface of the positive electrode. According to an exemplary embodiment, which may be combined with other embodiments described herein, the reactive gas may be selected from the group consisting of an oxygen-containing gas, a nitrogen-containing gas, or a combination thereof. Exemplary oxygen-containing gases that may be used in the embodiments described herein include oxygen (O2), ozone (O3), oxygen radicals (O4), and nitrogen-containing gases. * ), ionized oxygen atoms, carbon dioxide (CO2), nitric oxide (NO x ), water vapor, or a combination thereof. Exemplary nitrogen-containing gases that may be used in the embodiments described herein include N2, N2O, NO2, NH3, or a combination thereof. According to further embodiments, an additional gas, typically an inert gas such as argon, may be added to the gas mixture containing the reactive gas. Thereby, typically the amount of reactive gas can be more easily controlled. According to an exemplary embodiment, which may be combined with other embodiments described herein, the process comprises: * 10 -2 mbar to 1 * 10 -6 mbar (e.g., 1 * 10 -3 mbar or less, 1 * 10 -4 The method can be carried out in a vacuum environment with typical atmospheres of 0.1 MPa (0.25 mbar or less).
[0071] In operation 520, in some implementations, moist oxygen may be used as the reactive gas. Moist oxygen may be formed by flowing oxygen through a canister containing water vapor, which reacts with the evaporated material to form aluminum oxide hydroxide ((AlO(OH)), which is deposited on the surface of the electrode. Aluminum oxide hydroxide ((AlO(OH))) is typically found in diaspore ((α-AlO(OH)), boehmite, etc. TIFF0007599454000002.tif7170, or in the form of accdalite (5Al2O3·H2O). Without wishing to be bound by theory, not only is aluminum oxide hydroxide thermodynamically stable, but the hydrogen bonding also helps improve the bonding strength of the ceramic separator layer to the surface of the electrode.
[0072] In some embodiments, during operation 520, a plasma is formed from the reactive gas mixture. In some embodiments, the plasma is an oxygen-containing plasma. The oxygen-containing plasma reacts with the evaporated material to deposit a ceramic separator layer on the surface of the electrode. In one embodiment, the reactive gas mixture includes at least one of an oxygen-containing gas, an inert gas (e.g., argon, helium), or a combination thereof. In one embodiment, the oxygen-containing gas provided into the processing region includes oxygen (O2), ozone (O3), oxygen radicals (O4), or an inert gas (e.g., argon, helium), or a combination thereof. * ), ionized oxygen atoms, carbon dioxide (CO2), nitric oxide (NO x ), water vapor, or a combination thereof. Other oxygen-containing gases may be used. In some embodiments, the plasma is formed and delivered to the processing region using a remote plasma source.
[0073] In some embodiments, during operation 520, a gas source supplies oxygen gas (O2) through a mass flow controller to an ozone generator, which converts most of the oxygen into ozone gas (O3). The resulting oxygen-based mixture of O2 and O3, and possibly some oxygen radicals O *The ionized oxygen atoms or molecules are then delivered to a treatment region where the oxygen-based gas reacts with the surface of an electrode structure, which has been heated to a predetermined, preferably low, temperature. Ozone reacts with the surface of the electrode structure through the reaction O3 → O2 + O * is a metastable molecule that spontaneously and rapidly dissociates at * is a radical and reacts very rapidly with available substances that are oxidizable. Ozone generators can be implemented in many forms, including capacitively or inductively coupled plasma, or UV lamp sources.
[0074] In some implementations, if at least one edge of the positive and / or negative electrodes remains exposed, it may be desirable to deposit an additional ceramic edge coating on the exposed edge to avoid short circuits. The ceramic edge coating may comprise the same material as the ceramic separator layer. The ceramic edge coating may be deposited using a wet deposition method (e.g., slot die coating), followed by an optional drying and / or calendaring operation. The ceramic edge coating typically has a similar thickness as the ceramic separator layer. In one implementation, the edge coating process occurs before operation 510. In another implementation, the edge coating process occurs after operation 520.
[0075] In operation 530 , the negative and positive electrodes are bonded together with a ceramic separator layer between them to form a cell structure, such as cell structure 100 .
[0076] FIG. 6 shows a process flow diagram summarizing one embodiment of a method 600 for forming a cell structure according to one or more embodiments described herein. The cell structure may be, for example, the cell structure 200 shown in FIG. 2. Method 600 is similar to method 500, except that method 600 includes an operation 630 in which a gel polymer layer is deposited on either the surface of the negative electrode or the surface of the positive electrode. In some embodiments, the gel polymer layer is gel polymer layer 210. In some embodiments, the negative electrode is negative electrode 140 and the positive electrode is positive electrode 120. In some embodiments, ceramic separator layer 130 is deposited on a single electrode (e.g., the negative electrode or the positive electrode) and gel polymer layer 210 is deposited on the other electrode before joining the electrodes together.
[0077] In operation 610, the material to be deposited on at least one of the surfaces of the negative electrode and the positive electrode is subjected to an evaporation process to evaporate the material to be deposited in the processing region. Operation 610 may be performed similarly to operation 510. In operation 620, a reactive gas is flowed into the processing region to react with the evaporated material and form a ceramic separator layer on at least the surfaces of the negative electrode and the positive electrode. Operation 620 may be performed similarly to operation 520.
[0078] In operation 630, a gel polymer layer is deposited on at least one of the surface of the negative electrode and the surface of the positive electrode. The polymer of the gel polymer layer 210 can be selected from polymers currently used in the Li-ion battery industry. Examples of polymers that can be used to form the gel polymer layer include, but are not limited to, polyvinylidene difluoride (PVDF), polyethylene oxide (PEO), polyacrylonitrile (PAN), carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR), and combinations thereof. Without being bound by theory, it is believed that the gel polymer layer 210 can absorb the Li-conducting electrolyte to form a gel during device fabrication, which is beneficial for the formation of a good solid electrolyte interface (SEI) and also helps reduce resistance. The gel polymer layer 210 can be formed by dip coating, slot die coating, gravure coating, or printing. The polymer can also be deposited using Applied Materials Metacoat equipment. The dielectric polymer layer can have a thickness of about 5 nanometers to about 1 micrometer.
[0079] In operation 640, the negative and positive electrodes are bonded together with a ceramic separator layer and a gel polymer layer therebetween to form a cell structure, such as cell structure 200.
[0080] FIG. 7 shows a process flow diagram summarizing one embodiment of a method 700 for forming a cell structure according to one or more embodiments described herein. The cell structure can be, for example, cell structure 300 shown in FIG. 3. Method 700 is similar to method 600, except that a ceramic separator layer is deposited on both the positive and negative electrodes, and a gel polymer layer is deposited on one of the ceramic separator layers before bonding the negative and positive electrodes together. In some embodiments, the gel polymer layer is gel polymer layer 310a, the first ceramic separator layer is ceramic separator layer 330a, and the second ceramic separator layer is ceramic separator layer 330b. In some embodiments, the negative electrode is negative electrode 140 and the positive electrode is positive electrode 120.
[0081] In operation 710, the material to be deposited on at least one of the surface of the negative electrode and the surface of the positive electrode is subjected to an evaporation process to evaporate the material to be deposited in the processing region. Operation 710 may be performed similarly to operations 510 and 610. In operation 720, a reactive gas is flowed into the processing region to react with the evaporated material to form a first ceramic separator layer on the surface of the negative electrode and a second ceramic separator layer on the surface of the positive electrode. In some implementations, deposition on the negative electrode and the positive electrode may be performed in the same processing chamber or in separate processing chambers. In some implementations, deposition on the negative electrode and the positive electrode may be performed sequentially or simultaneously. Operation 720 may be performed similarly to operations 520 and 620.
[0082] In operation 730, a gel polymer layer is deposited on at least one of the first and second ceramic separator layers. The polymer of the gel polymer layer 310 can be selected from polymers currently used in the Li-ion battery industry. Examples of polymers that can be used to form the gel polymer layer include, but are not limited to, polyvinylidene difluoride (PVDF), polyethylene oxide (PEO), polyacrylonitrile (PAN), carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR), and combinations thereof. The polymer can also be a liquid crystal containing a salt such as Li2O. Without being bound by theory, it is believed that the gel polymer layer 310 can absorb Li conductive electrolyte to form a gel during device fabrication, which is beneficial for the formation of a good solid electrolyte interface (SEI) and also helps reduce resistance. The gel polymer layer 310 can be formed by dip coating, slot die coating, gravure coating, or printing. The polymer can also be deposited using Applied Materials Metacoat equipment. The dielectric polymer layer can have a thickness of about 5 nanometers to about 1 micrometer.
[0083] At operation 740, the negative electrode and the positive electrode are bonded together with the first ceramic separator layer, the gel polymer layer, and the second ceramic separator layer therebetween to form a cell structure, such as cell structure 300.
[0084] 8 shows a process flow diagram summarizing one embodiment of a method 800 for forming an electrode structure according to one or more embodiments described herein. The cell structure can be, for example, the cell structure 400 shown in FIG. 4. At operation 810, a negative electrode is provided. The negative electrode structure can be the negative electrode 140.
[0085] At operation 820, a lithium metal layer is formed on the negative electrode. The lithium metal layer can be the pre-lithiation layer 410. In one embodiment, an alkali metal film is formed on a substrate. In some embodiments, if the negative electrode 140 is already present, the pre-lithiation layer 410 is formed on the negative electrode 140. If the negative electrode 140 is not present, the lithium metal film can be formed directly on the negative current collector 150. Any suitable lithium metal film deposition process for depositing a thin film of lithium metal can be used to deposit the thin film of lithium metal. The deposition of the thin film of lithium metal can be by a PVD process such as evaporation, a slot-die process, a transfer process, screen printing, or a three-dimensional lithium printing process. The chamber for depositing the thin film of alkali metal can include a PVD system such as an electron beam evaporator, a thermal evaporator, or a sputtering system, a thin film transfer system (including a large area pattern printing system such as a gravure printing system), or a slot-die deposition system.
[0086] In operation 830, optionally, a protective layer is formed on the lithium metal layer. The protective layer can be the protective film 420. The protective film 420 can be a lithium fluoride film or a lithium carbonate film. In one embodiment, the protective film 420 is formed via an evaporation process. The material to be deposited on the substrate is exposed to an evaporation process to evaporate the material to be deposited in the processing region. The evaporation material can be selected from the group consisting of lithium (Li), lithium fluoride (LiF) (e.g., ultra-high purity single crystal lithium), aluminum oxide (AlOx), lithium carbonate (Li2CO3), or a combination thereof. Typically, the material to be deposited includes a metal such as lithium. Furthermore, the evaporation material can also be an inorganic compound. The evaporation material is a material that is evaporated during the evaporation process and coated with a lithium metal film. The material to be deposited (e.g., lithium fluoride) can be provided in a crucible. For example, lithium fluoride can be evaporated by a thermal evaporation technique or by an electron beam evaporation technique. This AlOx could be nm thick but potentially non-porous. Under some electrochemical conditions, ionically conductive Li-Al-O can be formed.
[0087] In some embodiments, the evaporation material is fed to the crucible in pellet form. In some embodiments, the evaporation material is fed to the crucible as a wire. In this case, the feed rate and / or wire diameter must be selected so that the desired ratio of evaporation material to reactive gas is achieved. In some embodiments, the diameter of the feed wire for feeding to the crucible is selected between 0.5 mm and 2.0 mm (e.g., between 1.0 mm and 1.5 mm). These dimensions may refer to several feed wires made of the evaporation material. Typical feed rates for the wire are in the range between 50 cm / min and 150 cm / min (e.g., between 70 cm / min and 100 cm / min).
[0088] The crucible is heated to generate vapor and coat the lithium metal film with a protective film. Typically, the crucible is heated by applying a voltage to the electrodes of the crucible, which are located on opposite sides of the crucible. Generally, according to the embodiments described herein, the material of the crucible is electrically conductive. Typically, the material used as the material of the crucible is temperature resistant up to the temperature used for melting and evaporation. Typically, the crucible of the present disclosure is made of one or more materials selected from the group consisting of metal borides, metal nitrides, metal carbides, non-metal borides, non-metal nitrides, non-metal carbides, nitrides, titanium nitrides, borides, graphite, tungsten, TiB2, BN, B4C, and SiC.
[0089] The material to be deposited is melted and evaporated by heating the evaporation crucible. Heating can be performed by providing a power source (not shown) connected to a first electrical connection and a second electrical connection of the crucible. For example, these electrical connections can be electrodes made of copper or a copper alloy. Heating is thus performed by an electric current flowing through the body of the crucible. According to other embodiments, heating can also be performed by a radiant heater of the evaporation device or an inductive heating unit of the evaporation device.
[0090] The evaporation unit according to the present disclosure can usually be heated to a temperature between 800 and 1200 degrees Celsius, for example 845 degrees Celsius. This is done by appropriately adjusting the current through the crucible or by appropriately adjusting the radiation. The crucible material is usually selected so that its stability is not adversely affected by the temperature in that range. The speed of the porous polymer substrate is usually in the range between 20 and 200 cm / min, more typically in the range between 80 and 120 cm / min, such as 100 cm / min. In these cases, the means for transport should be capable of transporting the substrate at these speeds.
[0091] In operation 840, the material to be deposited on at least one of the surface of the lithium metal layer and / or the surface of the protective layer is subjected to an evaporation process to evaporate the material to be deposited in the processing area. Operation 810 may be performed similarly to operations 510, 610, and 710. In operation 850, a reactive gas is flowed into the processing area to react with the evaporated material to form a ceramic separator layer on at least one of the surface of the lithium metal layer and / or the surface of the protective layer. The ceramic separator layer may be ceramic separator layer 430a. In some implementations, deposition on the negative electrode and the positive electrode may be performed in the same processing chamber or in separate processing chambers. In some implementations, deposition on the negative electrode and the positive electrode may be performed sequentially or simultaneously. Operation 720 may be performed similarly to operations 520 and 620.
[0092] Optionally, a gel polymer layer is formed on the ceramic separator layer. The gel polymer layer is gel polymer layer 440 and may be formed similarly to gel polymer layer 310 described in operation 730. The polymer of gel polymer layer 440 may be selected from polymers currently used in the Li-ion battery industry. Examples of polymers that may be used to form the gel polymer layer include, but are not limited to, polyvinylidene difluoride (PVDF), polyethylene oxide (PEO), polyacrylonitrile (PAN), carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR), and combinations thereof. Without being bound by theory, it is believed that gel polymer layer 440 can absorb Li-conducting electrolyte to form a gel during device fabrication, which is beneficial for the formation of a good solid electrolyte interface (SEI) and also helps reduce resistance. Gel polymer layer 440 can be formed by dip coating, slot die coating, gravure coating, or printing. The polymer can also be deposited using Applied Materials Metacoat equipment. The dielectric polymer layer can have a thickness of about 5 nanometers to about 1 micrometer.
[0093] The negative and positive electrodes are bonded together with ceramic separator layer 430a, gel polymer layer 440a, and ceramic separator layer 430b therebetween to form a cell structure, such as cell structure 400.
[0094] FIG. 9 illustrates a schematic diagram of an integrated processing tool 900 for forming a ceramic separator according to one or more embodiments described herein. In certain embodiments, the integrated processing tool 900 includes multiple processing modules or chambers 920 and 930 arranged in a row, each configured to perform one processing operation on a continuous sheet of material 910. In one embodiment, the processing chambers 920 and 930 are stand-alone modular processing chambers, with each modular processing chamber being structurally isolated from the other modular processing chambers. Thus, each stand-alone modular processing chamber can be independently positioned, rearranged, replaced, or maintained without affecting the other. In certain embodiments, the processing chambers 920 and 930 are configured to process both sides of the continuous sheet of material 910. Although the integrated processing tool 900 is configured to process a vertically oriented continuous sheet of material 910, the integrated processing tool 900 may also be configured to process substrates arranged in a different orientation, for example, a horizontally oriented continuous sheet of material 910. In certain embodiments, the continuous sheet of material 910 is a flexible conductive substrate.
[0095] In certain embodiments, the integrated processing tool 900 includes a transfer mechanism 905. The transfer mechanism 905 may include any transfer mechanism capable of moving a continuous sheet of material 910 through the processing regions of the processing chambers 920 and 930. The transfer mechanism 905 may include a common transport architecture. The common transport architecture may include a reel-to-reel system with a take-up reel 914 and a supply reel 912 for the system. The take-up reel 914 and the supply reel 912 may be heated separately. The take-up reel 914 and the supply reel 912 may be heated separately using an internal heat source or an external heat source disposed within each reel. The common transport architecture may further include one or more intermediate transfer reels (913a and 913b, 916a and 916b, 918a and 918b) disposed between the take-up reel 914 and the supply reel 912. Although the integrated processing tool 900 is shown as having a single processing area, in certain embodiments it may be advantageous to have separate or individual processing areas, modules, or chambers for each process. For embodiments having separate processing areas, modules, or chambers, the common transport architecture may be a reel-to-reel system in which each chamber or processing area has an individual take-up reel and supply reel, and one or more optional intermediate transfer reels disposed between the take-up reel and the supply reel. The common transport architecture may include a track system. The track system extends to the processing area or the individual processing areas. The track system is configured to transport either a web substrate or individual substrates.
[0096] The integrated processing tool 900 may include a supply reel 912 and a take-up reel 914 for moving a continuous sheet of material 910 through different processing chambers. The different processing chambers may include a first processing chamber 920 for depositing a ceramic separator film and a second processing chamber 930 for depositing a gel polymer layer on the ceramic separator film. In some implementations, the completed electrode will not be collected on the take-up reel 914 as shown in the figure, but may be directly integrated with a separator and positive electrode, etc., to form a battery cell.
[0097] The first processing chamber 920 is configured to deposit a ceramic separator film on the continuous sheet of material 910. In one embodiment, the first processing chamber 920 is an evaporation chamber. The evaporation chamber has a processing region 942 shown to include evaporation sources 944a, 944b (collectively 944) that may be disposed in a crucible and may be, for example, a thermal evaporator or an e-beam evaporator (not heated) in a vacuum environment. A first gas source 950 is coupled to the processing region 942 for supplying a reactive gas to the processing region 942. A remote plasma source 960 is coupled to the processing region for supplying a plasma to the processing region. The remote plasma source 960 may be coupled to a second gas source 970.
[0098] The second processing chamber 930 is configured to deposit a gel polymer layer onto the sheet of material (e.g., onto a ceramic separator membrane). The gel polymer layer can be an ionically conductive material as described herein. The gel polymer layer can be formed by dip coating, slot die coating, gravure coating, laminating, or printing.
[0099] In one embodiment, the second processing chamber 930 is a three-dimensional printing chamber. The printing chamber has a processing region 952 that is shown to include printing sources 954a, 954b (collectively 954) for printing a polymer ink.
[0100] In one embodiment, processing region 942 and processing region 952 remain under vacuum and / or at subatmospheric pressure during processing. The vacuum level of processing region 942 may be adjusted to match the vacuum level of processing region 952. In one embodiment, processing region 942 and processing region 952 remain at atmospheric pressure during processing. In one embodiment, processing region 942 and processing region 952 remain under an inert gas atmosphere during processing. In one embodiment, the inert gas atmosphere is an argon gas atmosphere. In one embodiment, the inert gas atmosphere is a nitrogen gas (N2) atmosphere.
[0101] Additional chambers may be included in the integrated processing tool 900. In some implementations, the additional chambers may provide for deposition of an electrolyte soluble binder, or in some implementations, the additional chambers may provide for formation of electrode materials (positive or negative electrode materials). In some implementations, the additional chambers provide for cutting of electrodes.
[0102] Figure 10A shows a scanning electron microscope (SEM) image 1000 of an uncoated cathode material. Figure 10B shows an SEM image 1010 of an aluminum oxide coated cathode material according to embodiments described herein.
[0103] FIG. 11 shows an SEM image of a schematic cross-sectional view of a cell structure 1100 having a ceramic separator layer formed according to embodiments described herein. The cell structure 1100 includes a ceramic separator layer disposed between a negative electrode and a positive electrode. The negative electrode is about 55 μm thick with an estimated porosity of less than 20%. The positive electrode (e.g., LiCoO2) is about 65 μm thick with an estimated porosity of about 17%. The ceramic separator layer is about 12-14 μm thick.
[0104] In summary, some of the advantages of the present disclosure include efficient deposition of the ceramic separator material directly onto the electrode material. Because the ceramic separator material can be deposited directly onto the electrode material, a polyolefin separator is not required. Eliminating the polyolefin separator reduces the distance between the positive and negative electrodes while reducing the possibility of thermal shrinkage. For example, in some embodiments, the ceramic separator layer formed according to the embodiments described herein is 3 μm or less in thickness compared to polyolefin separators that are typically about 20 μm or more in thickness. In addition, the dry coating techniques described herein do not suffer from some of the disadvantages that wet coating techniques suffer from. For example, wet coating techniques include solvents that often are adsorbed onto the underlying electrode structure, adding extra drying operations to the overall process. Furthermore, in some embodiments described herein, the process of ceramic separator layer deposition is a vacuum coating process that removes residual moisture from the electrode structure without adding additional drying components to the deposition process and processing tools.
[0105] When introducing elements of the present disclosure or example aspects or embodiments thereof, the articles "a," "an," "the," and "said" are intended to mean that there are one or more of the elements.
[0106] The terms "comprising," "including," and "having" are intended to be inclusive and mean that there may be additional elements other than the listed elements.
[0107] While the above is directed to embodiments of the present disclosure, other and further embodiments of the disclosure may be devised without departing from the basic scope thereof, the scope of the disclosure being determined by the claims which follow.
Claims
1. 1. A method of forming a separator for a battery, comprising: exposing a metal material deposited on a surface of a first electrode structure and a surface of a second electrode structure disposed in a processing region to an evaporation process to form an evaporated metal material, the metal material being aluminum (Al); flowing a reactive gas into the processing region to form a first ceramic separator layer on the surface of the first electrode structure and a second ceramic separator layer on the surface of the second electrode structure; exposing oxygen to water vapor to form moist oxygen; introducing said moist oxygen into said treatment area; flowing a reactive gas comprising: reacting the reactive gas with the evaporated metallic material to deposit the first ceramic separator layer on the surface of the first electrode structure and to deposit the second ceramic separator layer on the surface of the second electrode structure; wherein the first ceramic separator layer comprises a non-porous material and the second ceramic separator layer comprises a porous material. method.
2. The method of claim 1 , wherein the ceramic separator layer is an aluminum oxide hydroxide layer.
3. The method of claim 1 , wherein the evaporation process is a thermal evaporation process or an electron beam evaporation process.
4. The method of claim 1 , wherein the evaporation process includes exposing the metallic material to a temperature between 1300 degrees Celsius and 1600 degrees Celsius.
5. The method of claim 1 , wherein the first ceramic separator layer and the second ceramic separator layer have a thickness in the range of 1 nanometer to 3000 nanometers.
6. The method of claim 5 , wherein the thickness is in the range of 10 nanometers to 500 nanometers.
7. depositing a ceramic edge coating on an edge of at least one of the first electrode structure and the second electrode structure using a wet coating technique; The method of claim 1 further comprising:
8. The method of claim 7 , wherein depositing the ceramic edge coating occurs prior to exposing the metallic material to be deposited on the surface of the at least one of the first electrode structure and the second electrode structure.
9. 8. The method of claim 7, wherein depositing the ceramic edge coating occurs after depositing the first ceramic separator layer on the surface of the first electrode structure and depositing the second ceramic separator layer on the surface of the second electrode structure.
10. The method of claim 1 , wherein the first electrode structure is a negative electrode.
11. The method of claim 1 , wherein the second electrode structure is a positive electrode.
12. The method of claim 1 , further comprising depositing a gel polymer layer over at least one of the first ceramic separator layer and the second ceramic separator layer.
13. 1. A method of forming an electrode structure, comprising the steps of: exposing a metallic material deposited on a surface of a negative electrode and a surface of a positive electrode disposed in a processing region to a thermal evaporation process or an electron beam evaporation process to form an evaporated metallic material, the metallic material being aluminum (Al); flowing a reactive gas into the processing region; exposing oxygen to water vapor to form moist oxygen to form a first ceramic separator layer on the surface of the negative electrode and a second ceramic separator layer on the surface of the positive electrode; introducing said moist oxygen into said treatment area; flowing a reactive gas comprising: reacting the reactive gas with the vaporized metallic material to deposit the first ceramic separator layer on the surface of the negative electrode and the second ceramic separator layer on the surface of the positive electrode; wherein the first ceramic separator layer comprises a non-porous material and the second ceramic separator layer comprises a porous material. method.
14. 14. The method of claim 13, wherein the first ceramic separator layer comprises a non-porous lithium ion conducting material and the second ceramic separator layer comprises a porous lithium ion conducting material.
15. The method of claim 13 , wherein the negative electrode is composed of graphite or silicon-containing graphite.
16. The method of claim 12 , wherein the gel polymer layer comprises one or more gel polymer layers sandwiched between the first ceramic separator layer and the second ceramic separator layer.
17. The method of claim 13 , wherein the positive electrode is comprised of an intercalation compound, an insertion compound, or an electrochemically active polymer.
18. The method of claim 13 , further comprising depositing a gel polymer layer over at least one of the first ceramic separator layer and the second ceramic separator layer.
Citation Information
Patent Citations
Lithium-ion battery composite membrane with thermal shutdown function and preparation method
CN106654118A
Laminated body, and method for producing the same
JP2007023366A
Negative electrode, and battery
JP2009099328A
Nonaqueous secondary battery, and its manufacturing method thereof
JP2009163942A
Electrode and method of manufacturing electrode
JP2016225077A
